ON PHYTOCOENOTICAL MAPPING OF CASPIAN DESERT REGION - SAFRONOVA, I. (Annali di Botanica, 2004)
The phytoecological map (l :2.500.000) for Desert Region, including the Caspian Lowland and the Mangyshlak. has been compiled. It gives an idea of latitudinal differentiation cf vegetation. Edaphic variants and lithological composition in low mountains. The legend has been constructed according to zonal-typological principle e using an ecological-phytocoenotic classification. Heterogeneity of vegetation is reflected by means of territoria1 units (complex, series, combination) and additional marks above the vegetation background. In the northern subzone vegetation is fairly monotonous and characterized by prevalence of wormwood communities (Artemisia of subgenus Seriphidium), joined in three formations: Artemisia lerchiana, A. arenaria. A. pauciflora. Small areas are occupied by shrub deserts of Calligollum aphyllum and Tamarix ramosissima. To southward of 47° N in the middle subzone on the Caspian Lowland the communities of halophyte perennial saltworts essential1y dominate, and to less extent-wormwood communities of hemipsammophytic Artemisia terrae-albae and psammophytic Artemisia arenaria and A. lerchiana. Deserts of Mangyshlak are much diverse. Dwarf semishrubs are presented by species of perennial saltworts (Anabasis salsa, Nanophyton erinaceum,Arthrophytum lehnwnianum, Salsola orientaUs) and wonnwood (Artemisia terrae-albae, A. gurganica. A. santolina). To southward of 43° N in the southern subzone dwarf semishrub Salsola gemmascens and Artemisia kemrudica corrnnunities prevail.